(untitled) (Globalization and Business, 2023)
Many of the obstacles that Governments face in devel- oping countries in effectively managing domestic financial re- sources are due to structural conditions and related develop- ment problems. For example, a high concentration of wealth and high inequality of income are often associated with polit- ical processes and the weakening of the rule of law. Similarly, dependence on the exploitation of natural resources can lead to unpredictability and instability in the structure of public rev- enues, which limits the ability of the state to plan and main- tain the level of investment consistent with long-term devel- opment goals. Measures aimed at strengthening the public financial management system and, therefore, mobilizing domestic public resources should be carried out taking into account these various problems, often of a structural nature. Important for the success and effectiveness of tax reforms in most develop- ing countries is the recognition that the development of ad- ministrative and institutional capacity at the national level is a complex and time-consuming process, the results of which will not be immediately apparent. To create such a potential, developing countries may often lack resources, expertise and political stability. This will require concerted efforts of the in- ternational community to help them find the necessary hu- man and financial resources to support measures aimed at improving the overall system of public finance regulation and mobilizing domestic public resources.